2018
DOI: 10.1177/1559325818785564
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low-Dose Occupational Exposure to Ionizing Radiation on T-Cell Populations and Subpopulations and Humoral Factors Included in the Immune Response

Abstract: The aim of the present study is to assess the effects of low-dose occupational exposure on T helper response. One Hundred five employees working in Nuclear Power Plant, Kozloduy, Bulgaria and control group of 32 persons are included in this investigation. Flow cytometry measurements of T-cell populations and subpopulations and natural killer T cells are performed and levels of G, A, and M immunoglobulins and interleukin 2 (IL-2), IL-4, and interferon γ were determined. The data interpreted with regard to cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Although these outcomes appear promising, and although potential efficacy mechanisms are well delineated for COVID-19, these findings remain preliminary and require confirmation through randomized trials. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Additional immunologic analyses of these and other cytokines and immune markers was performed and will be forthcoming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these outcomes appear promising, and although potential efficacy mechanisms are well delineated for COVID-19, these findings remain preliminary and require confirmation through randomized trials. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Additional immunologic analyses of these and other cytokines and immune markers was performed and will be forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 8 Numerous prior articles have described the mechanistic pathways whereby low-dose radiation therapy (LD-RT) could provide a therapeutic advantage. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 The first exploration into this intervention, a 7-day interim safety analysis of 5 initial patients treated on a phase 1 trial, investigated safety of LD-RT using a dose of 1.5 Gy with no detected acute toxicity or reflex exacerbation of the cytokine storm. 17 Preprint publication of this safety data was first released on June 8, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-Inflammatory effects of LD-RT can result in apoptosis and decrease adhesion of the leukocytes to endothelial cells, 10 mitigate proinflammatory effects of macrophages by reducing secretion of nitric oxide and reactivation oxygen species, 11 and induce polarization of M1inflammatory macrophages to M2-anti-inflammatory subtype. 12 LD-RT may also reduce TNF-α, IL-1β, IL-2, IL-6, IL-8, and INF-γ, [13][14][15][16][17] which are thought to be increased in COVID-19 cytokine storm. While these findings require further investigation, whole-lung LD-RT did not induce post-treatment pancytopenia or immunosuppression and therefore is unlikely to slow viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Anti-Inflammatory effects of low-dose radiation therapy (LD-RT) can result in apoptosis and decrease adhesion of the leukocytes to endothelial cells, 10 mitigate proinflammatory effects of macrophages by reducing secretion of nitric oxide and reactivation oxygen species, 11 and induce polarization of M1-inflammatory macrophages to M2-anti-inflammatory subtype. 12 Furthermore, LD-RT may also reduce TNF-α, IL-1β, IL-2, IL-6, IL-8, and INF-γ, [13][14][15][16][17] which are thought to be increased in the COVID-19 cytokine storm. Thus, it was hypothesized that LD-RT directed at the lungs may dampen the cytokine hyperactivation and improve the outcome of COVID-19 hospitalized and oxygen-dependent patients.…”
Section: Introductionmentioning
confidence: 99%
“…The main added value of this study compared to the previous ones was that a) it took into account confounding factors such as smoking and alcohol consumption and b) it discussed the influence of aging as another confounding factor on immune parameters, which can overlap with certain changes seen following radiation. Though, they also showed that most of the changes in the measured parameters remained within the normal reference values illustrating the discrete effects of low doses ( Gyuleva et al, 2018 ; Gyuleva et al, 2015a ; Gyuleva et al, 2015b ). Other occupational data are from interventional cardiologists, radiologists and radiation workers.…”
Section: Human Biomonitoring and Epidemiological Data On Low Dose Radiation-induced Immunological Changesmentioning
confidence: 95%